ANALISIS KOMPARASI BIAS DALAM JURNALISME ONLINE PADA MEDIA KOMPAS, KUMPARAN DAN ANTARA - Hari Jummaulana; Sartika Sartika; Zefa Destiana (Ensiklopedia of Journal, 2026)
Media coverage prioritizes journalists' professionalism, but in reality, bias is still found in many media outlets, both in the news and in the characteristics of the media. This study examines media bias through a comparative analysis of online journalism in Antara, Kompas, and Kumparan. The research method uses a qualitative descriptive approach with a literature review approach. The analysis uses a comparison table matrix method between media outlets, based on the intensity of news publication, media characteristics, and the determination of news titles and content. Through this analysis, it was found that each news outlet is not the same in producing news. The media comparison is intended to make it easier for readers to digest information that each media outlet has its own differences and characteristics.Keywords: Comparison, Bias, Media, Online Journalism